2013
DOI: 10.4172/2329-9029.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Nitrogen Co-ordinately Improve Photosynthetic Efficiency, Growth and Proline Accumulation in Two Cultivars of Mustard Under Salt Stress

Abstract: Material and Methods Plant material and treatments Seeds of Alankar and Chutki cultivars of mustard (Brassica juncea L.Czern & Coss.) were surface sterilized and were sown in 23 cm diameter earthen pots containing soil composed of peat and compost (4:1, w/w) mixed with sand (3:1, w/w). The pots were kept in green house of the Botany Department, Aligarh Muslim University, Aligarh under natural day/night conditions with day/night temperatures of 22/12 ± 3°C, photo synthetically active radiation (PAR), 900 ± 25 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…The increased N and S assimilation in plants treated with SA resulted in increased chlorophyll and proline synthesis. Rais et al (2013) have shown that both individual and combined applications of N and S resulted in increased NRA, N content, and proline accumulation and alleviated salt stress effects on photosynthetic efficiency and growth of B. juncea. Moussa and Khodary (2003) reported that spraying of salicylic acid caused significant increases in the activity of both Rubisco enzyme and photosynthetic pigments under drought stress.…”
Section: Discussionmentioning
confidence: 98%
“…The increased N and S assimilation in plants treated with SA resulted in increased chlorophyll and proline synthesis. Rais et al (2013) have shown that both individual and combined applications of N and S resulted in increased NRA, N content, and proline accumulation and alleviated salt stress effects on photosynthetic efficiency and growth of B. juncea. Moussa and Khodary (2003) reported that spraying of salicylic acid caused significant increases in the activity of both Rubisco enzyme and photosynthetic pigments under drought stress.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the importance of major mineral nutrients in the agricultural system, most of these have been employed to improve the level of accumulation of osmo‐compatible organic solutes and strengthen the antioxidant machinery in salt‐exposed plants (Nazar et al , Khan et al ). Among mineral nutrients, nitrogen (N) and sulfur (S) are crucial macronutrients important for plant growth and development and show regulatory interactions (Kaur et al , Rais et al , Qiao et al ). N and S are involved in the synthesis of vital organic compounds including amino acids and proteins synthesis (Hesse et al , Scherer ).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is not only a vital macronutrient for cotton production [14,28,29], but also the next crucial input factor for better crop production after water [30]. Moreover, nitrogen governs many cellular activities in plants since it is part of key components of chlorophyll, amino acids, proteins, nucleic acids, enzymes, plant hormones, and osmolytes [17,27], all of which are involved in plant salt tolerance mechanisms through different pathways [31,32]. NO 3 − and NH 4 + are the most common inorganic forms of nitrogen, and plants usually uptake these by their roots and use them for their metabolic activities [33].…”
mentioning
confidence: 99%